Synergistic effect of CART (cocaine- and amphetamine-regulated transcript) peptide and cholecystokinin on food intake regulation in lean mice - Maletínská, Lenka; Maixnerová, Jana; Matysková, Resha; Haugvicová, Renata; Pirník, Zdeno; Kiss, Alexander; Zelezná, Blanka (BMC neuroscience, 2008)
BACKGROUND: CART (cocaine- and amphetamine-regulated transcript) peptide and cholecystokinin (CCK) are neuromodulators involved in feeding behavior. This study is based on previously found synergistic effect of leptin and CCK on food intake and our hypothesis on a co-operation of the CART peptide and CCK in food intake regulation and Fos activation in their common targets, the nucleus tractus solitarii of the brainstem (NTS), the paraventricular nucleus (PVN), and the dorsomedial nucleus (DMH) of the hypothalamus. RESULTS: In fasted C57BL/6 mice, the anorexigenic effect of CART(61-102) in the doses of 0.1 or 0.5 microg/mouse was significantly enhanced by low doses of CCK-8 of 0.4 or 4 microg/kg, while 1 mg/kg dose of CCK-A receptor antagonist devazepide blocked the effect of CART(61-102) on food intake. After simultaneous administration of 0.1 microg/mouse CART(61-102) and of 4 microg/kg of CCK-8, the number of Fos-positive neurons in NTS, PVN, and DMH was significantly higher than after administration of each particular peptide. Besides, CART(61-102) and CCK-8 showed an additive effect on inhibition of the locomotor activity of mice in an open field test. CONCLUSION: The synergistic and long-lasting effect of the CART peptide and CCK on food intake and their additive effect on Fos immunoreactivity in their common targets suggest a co-operative action of CART peptide and CCK which could be related to synergistic effect of leptin on CCK satiety.
Keywords: sinkalid; receptor cholecystokininu A; myši; Nerve Tissue Proteins; antagonisté hormonů; Male; Drug Synergism; fenylmočovinové sloučeniny; Devazepide; synergismus léků; peptidové fragmenty; Injections, Intraperitoneal; devazepid; Sincalide; regulace chuti k jídlu; Mice; Animals; Exploratory Behavior; Proto-Oncogene Proteins c-fos; Dose-Response Relationship, Drug; Receptor, Cholecystokinin A; Receptor, Cholecystokinin B; myši inbrední C57BL; receptor cholecystokininu B; kokainem a amfetaminem regulovaný transkript; Peptide Fragments; zvířata; benzodiazepinony; Hormone Antagonists; nucleus solitarius; Appetite Regulation; proteiny nervové tkáně; mužské pohlaví; Benzodiazepinones; Mice, Inbred C57BL; nucleus paraventricularis hypothalami; neurony; injekce intraventrikulární; Phenylurea Compounds; protoonkogenní proteiny c-fos; hubenost; vztah mezi dávkou a účinkem léčiva; Paraventricular Hypothalamic Nucleus; pátrací chování; Solitary Nucleus; Cocaine- and Amphetamine-Regulated Transcript Protein; Neurons; nucleus dorsomedialis hypothalami; Dorsomedial Hypothalamic Nucleus; Thinness; injekce intraperitoneální; Injections, Intraventricular